Renewable Energy Promotion Instruments Used by Innovation Brokers in a Technology Transfer Network. Case Study of the Enterprise Europe Network - Zofia Gródek-Szostak; Marcin Suder; Rafał Kusa; Anna Szeląg-Sikora; Joanna Duda; Marcin Niemiec (Energies, 2020)
Stable and sustainable economic development—including that of renewable energy resources (RES)—requires institutional support of an environment that would enable market operations, and support them in case they are ineffective. Innovation brokers, including structured technology transfer networks, play a key role in promoting, disseminating, and liaising between the parties in the RES sector. The aim of the paper is to present the structure of events used to promote RES in Europe by the Enterprise Europe Network in the years 2017–2018; to verify whether the type of promotion instrument used is significantly related to the location of the events organized; to research whether the selection of the supporting partner is determined by the organized event’s geographical location. The analysis is carried out by means of an empirical study of the network of innovation brokers, i.e., the Enterprise Europe Network. Additionally, the available data are analyzed in terms of the type of the partner supporting individual events. It has been shown that there is a significant variation in the structure of the types of events for individual regions of Europe. This could mean that the organizers’ decisions as to the type of events organized in particular regions of Europe are deliberate and in some way adjusted to the region in which they take place.